Rating of Debt Instruments - A Model for Evaluation - Viyyanna Rao, K.; Maruthi Varaprasad, A. (Indian Journal of Finance, 2011)
Credit rating is slowly emerging as one of the significant financial services. In times of capital markets emerging in countries like India, there is an imminent need for rating of both instruments and institutions. The Indian capital market has been exhibiting the required stability, even when Asian and American markets are facing rough weather. The capital market reforms initiated by the government over the past decade, and half have started yielding the results. In order that there should be momentum among the investing public, and they are attracted towards stock markets, every service institution must contribute its own mite for the deepening of the investment process. In this context, credit rating, being a reliable service, can be of immense help to the investors as well as to the issuing companies. This turns out to be all the more significant in the circumstance of market turbulence as of today. This paper attempted to evaluate the ratings of the long- term debt instruments with the help of a methodology developed by the researchers. The methodology adopted in the present study to test ratings proved 60 percent uniformity with the ratings awarded by CRISIL. The remaining 40 percent variation could be ascribed to the influence of qualitative factors. The investigator also found that there is no significant difference between the performance of the issuers in the pre-rating period and post-rating period.